The Implementation of Organizational Culture Based on Tri Hita Karana in the Effort to Realize the Organizational Performance in PDAM Buleleng Regency - Luh Kartika Ningsih; Ni Luh Putu Eka Yudi Prastiwi; Ni Made Sri Ayuni (International Journal of Social Science and Business, 2019)
This study aims to determine the role of Organizational Culture based on Tri Hita Karana in the effort to realize Organizational Performance by taking into account other factors such as Human Resource Management, Total Quality Management, and Employee Performance. This study uses a quantitative approach. The data analysis technique used in this study is a structural equation model (SEM) based on variance or Component based SEM, known as Partial Least Square (PLS) Visual version 3.2.7. The number of samples used was 48 people with t-table values for significance levels α = 0.05 and degree of freedom (df) = 46 is 2.58. The results show that there are two relationships that show significant results, namely the role of Organizational Culture based on Tri Hita Karana on Employee Performance has a value of 17.353 with t-statistics > t-table (17.353 > 2.58). And the same results are also shown in the relationship between Total Quality Management and Organizational Performance with a value of 8.232 > 2.58. Different results are shown in 4 other relationships, namely the influence of the organization's culture on organizational performance, the influence of HRM on organizational performance, the influence of HRM on employee performance, and the influence of total quality management on employee performance with t-statistics < t- table (0.220 < 2.58), (0.544 < 2.58), (0.866 < 2.58), and (0.553 < 2.58). From the results of this study it can be seen that there are still several factors that have not been able to provide a significant value on organizational performance in the PDAM Buleleng.